Knowledge, Attitude and Practices towards Oral Hygiene among Adults (18-45yrs) in Lira Regional Referral Hospital, Lira City. A Cross-sectional Study. - Henry Okello; Vincent Charles Kalungi (Student's Journal of Health Research, 2022)
Background: Oral hygiene is maintaining the cleanliness of the mouth and taking care of teeth and gum. The purpose of the study was to assess the knowledge, attitude, and practices toward oral hygiene among patients aged 18-45 years in Lira Regional Referral Hospital, Lira district.  Methodology: The study employed a cross-section design to address the specific objectives of the study on a sample of 50 respondents using the simple random technique. A semi-structured questionnaire was designed and used as a data collection tool. Results:  From the study findings, the majority (86%) of the respondents knew about oral health, most (40%) of the respondents reported dentists as their source of information about oral hygiene, and the majority (92%) went for dental checkups to dentists, the majority (86%) knew about dental caries and most (68.9%) gave the correct response about what dental caries are, the majority (92%) reported that they knew the causes of dental caries and more than half (60%) gave the correct response about the cause of dental caries.  Conclusion:  Even though the respondents had good knowledge and positive attitudes toward oral hygiene, surprisingly they were at risk of contracting dental caries and other periodontal conditions because their oral hygiene practices were below the global recommendations and most of them used only toothbrushes to clean their teeth.  Recommendation:  The ministry of health should emphasize oral and dental care health education in health facilities and hospitals or carry out health camps and community outreaches. This would at least ensure that the general public gets access to basic knowledge about oral health and hygiene practices and can identify the signs and symptoms of oral health conditions as well as prevent them.